Problem and pro-social behavior among Nigerian children with intellectual disability: the implication for developing policy for school based mental health programs - Bakare Muideen O; Ubochi Vincent N; Ebigbo Peter O; Orovwigho Andrew O (BMC, 2010)
Abstract Background School based mental health programs are absent in most educational institutions for intellectually disabled children and adolescents in Nigeria and co-morbid behavioral problems often complicate intellectual disability in children and adolescents receiving special education instructions. Little is known about prevalence and pattern of behavioral problems existing co-morbidly among sub-Saharan African children with intellectual disability. This study assessed the prevalence and pattern of behavioral problems among Nigerian children with intellectual disability and also the associated factors. Method Teachers' rated Strengths and Difficulties Questionnaire (SDQ) was used to screen for behavioral problems among children with intellectual disability in a special education facility in south eastern Nigeria. Socio-demographic questionnaire was used to obtain socio-demographic information of the children. Results A total of forty four (44) children with intellectual disability were involved in the study. Twenty one (47.7%) of the children were classified as having behavioral problems in the borderline and abnormal categories on total difficulties clinical scale of SDQ using the cut-off point recommended by Goodman. Mild mental retardation as compared to moderate, severe and profound retardation was associated with highest total difficulties mean score. Males were more likely to exhibit conduct and hyperactivity behavioral problems compared to the females. The inter-clinical scales correlations of teachers' rated SDQ in the studied population also showed good internal consistency (Cronbach Alpha = 0.63). Conclusion Significant behavioral problems occur co-morbidly among Nigerian children with intellectual disability receiving special education instructions and this could impact negatively on educational learning and other areas of functioning. There is an urgent need for establishing school-based mental health program and appropriate screening measure in this environment. These would afford early identification of intellectually disabled children with behavioral problems and appropriate referral for clinical evaluation and interventions. The need to focus policy making attention on hidden burden of intellectual disability in sub-Saharan African children is essential.